النظام القانوني للرقابة والضبط الجمركية باستخدام التكنولوجيا الحديثة - Mohammad Abdallah Mohamed Al Ali; Hasnizam Hashim; Muhammad Nizam Awang (Al Hikmah Research and Publication Centre, 2024)
Non-Indexed Publication